The Influence of Discipline on Work Performance of J&T Express Employees at Sukahaji Branch, Majalengka Regency - Utomo, Sudibyo Budi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to find out and obtain the data and information needed to process, analyze and interpret disciplinary problems that can affect employee work performance. The object of this research is the employees of J&T Express Sukahaji Branch, Majalengka Regency. The research method used is descriptive and verification methods. The sample in this study was 25 respondents using saturated sampling. Data collection techniques are by using questionnaires, interviews and observation. Data instrument testing is carried out by means of validity testing, reliability testing, data normality testing, correlation coefficient analysis, regression coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this research state that: (1) discipline at the J&T Express Sukahaji Branch in Majalengka Regency has reached more than 60% which is proven, namely 77.1% or tcount > ttable (40.768 > 1.701). (2) work performance at J&T Express Sukahaji Branch in Majalengka Regency has reached more than 60% which is proven, namely 79.5% or tcount > ttable (51,642 > 1,701). (3) Discipline has a positive and significant effect on employee work performance at the J&T Express Sukahaji Branch in Majalengka Regency, because tcount > ttable (3.810 > 1.713). From the research results, it can be concluded that discipline influences employee work performance, this is proven by the calculation results of the tcount value being greater than ttable (3.810) > (1.713). The magnitude of the influence of discipline on the work performance of J&T Express Sukahaji Branch employees in Majalengka Regency is 38.7%, while the remaining 61.3% is influenced by other factors not researched by the author.